Isoxazolidines as Biologically Active Compounds - Chiacchio, M.A.; Giofrè, S.V.; Romeo, R.; Romeo, G.; Chiacchio, U. (Current Organic Synthesis, 2016)
This review is focused on the synthesis of isoxazolidines as the core of biologically active compounds having anti-cancer, antiviral, antibacterial and anti-inflammatory properties. The isoxazolidine ring, as mimetic of ribose, has been principally synthesized with high regio-, stereo- and enantioselectivity, applying the methodology of 1,3-dipolar cycloaddition, involving nitrones and alkenes as dipoles and dipolarophiles, respectively. The easy accessibility of this ring by this approach, then, makes this heterocycle, particularly suitable for the synthesis of small molecules useful in the design of new and modified drugs.
Keywords: antiviral agents